PERTUMBUHAN DAN PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA PENAMBAHAN DUA SUMBER NUTRISI - Afina Shifriyah; Kaswan Badami; Sinar Suryawati (Agrovigor, 2012)
White oyster mushroom (Pleurotus ostreatus) harvest tend to reduced because  of  nutrients decreasing in the  growth media.  An effort  to increase its  production    is by adding nutrients  into  the growth media. This research aims to determine the effect of  nutrition  on growth  and production of  white oyster mushrooms. The nutrients used in this study is monosodium glutamate (MSG) and old  coconut  water.      The research method  used was  Complete Randomized Design  (CRD)  analysis  of variance  with  orthogonal  contrasts.  The treatments tested is the addition of nutrients after 3 times the harvest consists of four levels: control  (without  giving  nutrient solution), the provision of  nutrient solution Monosodium  glutamate  (MSG) 0.4%,  30%  old  coconut  water  and  nutrient combination of  MSG and old coconut water.  The results show that the addition of nutrients was not significantly different to the parameters of the total fresh weight, total  weight, mean  stalk  length,  average  diameter of  the bodies  and  biological efficiency of fruit.   However, it  significantly different  to the  parameters of maximum  hood width  average  and  buds  appearance time.   Based on  these observations we can conclude that feeding monosodium glutamate, old  coconut  water   and  combination of nutrients  monosodium  glutamate  and  old  coconut water  significantly  affect to maximum hood width  average  and  buds  appearance time.    Nutrition  as well as  without being given nutrients (control) of  body fresh  weight.  Nutrition old coconut water is better  than Monosodium  glutamate to maximum hood width average.  Monosodium glutamate or old coconut water nutrition  is better  than the  combination of nutrients monosodium  glutamate  and old  coconut  water  to the  long  shoots  appear.  Nutrition  increase wet weight up to 1.89%.